Ferme gauloise et établissements ruraux gallo-romains du Bois de l’Homme Mort, Saint-Pathus (Seine-et-Marne) milieu iie s. av.-début ve ap. J.-C. - Gilles Desrayaud (Revue Archéologique du Centre de la France)
Excavations at the Bois de l’Homme Mort locality, near the French village of Saint-Pathus, in northern Seine-et-Marne, have unveiled more than five centuries of rural antiquityA Gallic farm and three Gallo-Roman rural settlements, one of which could include a sacred edifice, were brought to light on a 130 acre area. Even though the enclosures and facilities are of modest size, they nonetheless bear witness to the dynamism of the territory between the ancient cities of Meaux (IANTINUM) and Senlis (AUGUSTOMACUS), north-east of the Paris area, The paleo-environmental studies outline a largely open countryside, made up of fields and meadows, where diversified cereal crops predominate.No stratigraphic settlement traces antedating the Latenian period have been detected. After the final desertion of the Gallo-Roman sites, around the beginning of the 5th c. AD, the disappearance of any substantial rural activity seems to be associated with forest recovery.